RNA-Primed DNA Synthesis In Vitro - Keller, Walter (1972)
In vitro DNA synthesis on single-stranded circular DNA can be initiated by RNA primers. RNA chains are covalently extended by DNA polymerase II from KB cells and DNA polymerase I from Micrococcus luteus, but not by an RNA-dependent DNA polymerase from avian myeloblastosis virus. The reaction product consists of DNA chains with a piece of RNA at their 5′-ends, hydrogen bonded to the template DNA. The primer RNA is linked to the product DNA via a 3′:5′-phosphodiester bond, and can be specifically removed by ribonuclease H. The possible role of ribonuclease H in RNA-primed DNA synthesis in vivo is discussed.